Modulation of Neural Activity for Myelination in the Central Nervous System - Choi, Elliot H.; Blasiak, Agata; Lee, Joonho; Yang, In Hong (Frontiers in Neuroscience, 2019)
Electrical stimulation has been playing a significant role in revealing various functions and mechanisms of the nervous system. It is no different for myelination, a process in which oligodendrocytes in the central nervous system (CNS) or Schwann Cells in the peripheral nerve system (PNS) wrap around axons to provide an insulating layer in vitro and in vivo. It has been widely recognized that the myelin sheath accelerates axon signal conduction and provides neuroprotection. Recent studies have begun to reveal its role in plasticity. The major mechanism that enables this process is activity-dependent myelination – the phenomenon where neuronal activity supports oligodendrocyte maturation and myelin sheath formation. In light of recent discoveries, a better understanding of this phenomenon has a potential to provide therapeutic targets for not only demyelinating diseases, but also psychiatric disorders. There is a growing need for experimental platforms capable of dissecting the effect of neural activity on myelination in health and disease. The effect of neural activity is commonly studied by comparing the myelination levels in cultures with neurons of low and high activity. Electrical stimulation is particularly well suited as a method of inducing neural activity in these systems. In this review, we describe in vitro platforms for studying activity-dependent myelination, which utilize neuron stimulation via electrical field. We also discuss stimulation profiles, as well as the alternatives to electrical stimulation in the context of regular, compartmentalized, and organotypic co-cultures.